Local citizens interpersonal communication with refugees in Pekanbaru City, Indonesia - Happy, Wulandari (2019)
This study aims to explore the interpersonal communication of Pekanbaru City local citizens with refugees around them. This research conducted to find out the motives, the behaviors and the local’s preferences when communicate with refugees. The result of the study is expected to contribute on Indonesian government discussion of designated island to accommodate refugees who are live and will come to Indonesia. So, this study believes that there should be any thorough research about the local citizen acceptance toward the issue. Because at the end of the day, refugees who come to a host country will affects the local society in their life. However, the lack of study on host community and refugees in Indonesia especially based on the local citizens’ point of view do not fulfilled specific data of them while this study believes that the variable from each area has to be particular because having various cultures could lead local citizens to different behaviors on dealing with social dynamics. Therefore, this study used phenomenology in qualitative to gain specific data from local citizen’s experiences when communicating with refugees. By studying the interpersonal communication between local community and refugees thoroughly and putting the experience into a pattern or concept may contribute to a government and any related institution for future strategy to enter and convey a plan to a group of people so it could be more efficient and targeted. Data is collected by using semi-structured interview and observation on five suitable informants based on purposive sampling. The framework analysis is used for data transcription while discourse analysis is used for data from observation. As a result, the first objective which is the motive of communication has found that local citizen communicates purposely for inclusion, to show friendliness, and to sell certain items as they see refugees as their potential customers. The second objective which focus on the communication behavior, informants seen to have prominent behavior such as high understanding, tolerance and committed to avoid problems in their communication with refugees. Then, the third objective resulted in language barrier and lack of understanding in honorific usage as the disruption aspects while understanding and familiarity work as supportive aspects.